'Common law-ization of criminal law'? The evolution of nullum crimen sine lege and the forthcoming challenges. Issue 3 (September 2017) - Manes, Vittorio
This article focuses on the cross-constitutional influences pursued by the European Court of Human Rights (ECtHR) case law which modify the Constitutional assets of the Italian legal order, reconsidering the nullum crimen sine lege. The outline is a hybrid model, resulting from the contamination of several common law patterns, which requires the traditional categories to be shaped into the judicial lawmaking approach and the stare decisis doctrine.